The Role of Suicide Literacy and Suicide Stigma in Shaping Attitudes toward Seeking Professional Psychological Help among Indonesian Emerging Adults - Revata, Bryan Kim; Djaja, Ngadiman (Journal of Educational, Health and Community Psychology, 2025)
Suicide is the fourth leading cause of premature death among emerging adults, with significant implications for public health. In Indonesia, the prevalence of suicide cases has reached 6,544, although this figure likely underrepresents the true extent of the issue. Alarmingly, only a small percentage of Indonesian adolescents, approximately 2.6%, seek psychological assistance despite the pressing need for mental health support. This study investigates the roles of suicide literacy and stigma in shaping attitudes toward seeking professional psychological help. Data were collected through an online survey involving 397 respondents. The analysis utilized multiple linear regression to assess the contributions of suicide literacy, stigma, and various demographic factors to attitudes towards seeking professional psychological help. Findings indicated that while suicide literacy, stigma, and demographic variables collectively contribute to attitudes toward seeking professional help, only suicide stigma and demographic factors (college major and family relation) significantly influenced these attitudes. This study underscores the critical need to address and reduce suicide stigma as a means of fostering positive attitudes toward seeking professional psychological help among emerging adults in Indonesia.